Jawabanmu

2014-06-23T21:58:43+07:00
F(x)=x³+px²+qx+10=0
(x-1)=0
x=1
maka
f(1)=(1)³+p(1)²+q(1)+10=0
f(1)=p+q=-11
(x-2)=0
x=2
f(2)=(2)³+p(2)²+q(2)+10=0
f(2)=8+4p+2q+10=0
f(2)=4p+2q=-18
eliminasi nilai p dan q dari persamaan f(1) dan f(2)
p=2, q=-13
2p-q=2(2)-(-13)=4+13=17
 \lim_{x \to \ 9} \frac{(x-9)( \sqrt{x} -1)}{ \sqrt{x} -3}= \frac{ (\sqrt{x}-3)( \sqrt{x}+3)( \sqrt{x} -1  }{ \sqrt{x} -3}  =  \lim_{x \to \ 9}  ( \sqrt{x} +3)( \sqrt{x} -1)
 \lim_{n \to \ 9} x+2 \sqrt{x} -3=(9)+2 \sqrt{9} -3=9+6-3=12